2021
DOI: 10.21203/rs.3.rs-478258/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delayed Fluorescence from Inverted Singlet and Triplet Excited States for Efficient Organic Light-Emitting Diodes

Abstract: Hund’s multiplicity rule states that for a given electronic configuration, a higher spin state has a lower energy. Rephrasing this rule for molecular excited states predicts a positive energy gap between spin-singlet and spin-triplet excited states, which has been consistent with numerous experimental observations over almost a century. Here, we report a fluorescent molecule that disobeys Hund’s rule, possessing a negative singlet–triplet energy gap of –11 meV. The energy inversion of the singlet and triplet e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Results obtained in experimental studies on chemical derivatives of this class of molecules agree with the theoretically predicted reverse order of the lowest singlet and triplet states. 3,6,11 The inverted singlettriplet gap, often abbreviated INVEST, makes these molecules interesting not only from fundamental research point of view, but also as promising candidate molecules for use in photophysical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Results obtained in experimental studies on chemical derivatives of this class of molecules agree with the theoretically predicted reverse order of the lowest singlet and triplet states. 3,6,11 The inverted singlettriplet gap, often abbreviated INVEST, makes these molecules interesting not only from fundamental research point of view, but also as promising candidate molecules for use in photophysical applications.…”
Section: Introductionmentioning
confidence: 99%
“… 30 Recently, Miyajima et al experimentally confirmed inverted singlet–triplet gaps in heptazine derivatives. 31 While many correlated wave function-based electronic structure methods have predicted inverted singlet–triplet gaps qualitatively correctly, one of the most widely used excited-state electronic structure method, LR-TDDFT, has failed to predict the inversion of singlet–triplet gaps. Computational studies, in the past, pointed toward the inability of LR-TDDFT to incorporate double excitations by going beyond adiabatic approximation 32 as the source of this error.…”
Section: Introductionmentioning
confidence: 99%
“…However, some N-doped triangulate molecules have been shown to violate Hund's rule by having inverted singlet-triplet gaps (ΔEST < 0) . 15,16 These materials benefit from the efficient reverse intersystem crossing process from T1 to S1 state, leading to substantial fluorescence rates, thus, in turn, suitable candidates for TADF materials.…”
Section: Introductionmentioning
confidence: 99%